Micro solid‐phase derivatization analysis of low‐molecular mass aldehydes in treated water by micellar electrokinetic chromatography. Issue 6 (29th January 2014) - Fernández‐Molina, José María; Silva, Manuel
<x xml:space="preserve">Abstract</x> A MEKC method was developed for the determination of aliphatic and aromatic low‐molecular mass aldehydes (LMMAs) in treated water samples. The method involves the precapillary derivatization and extraction of the aldehydes on a Telos™ENV μ‐SPE column impregnated with 2, 4‐dinitrophenylhydrazine . After elution of the hydrazones with ACN, the derivatives were analyzed using MEKC–DAD. Resolution of the MEKC procedure was studied by changing the pH and the concentration of the buffer, the type, and the concentration of surfactant, and the organic modifier content in the BGE. A running buffer consisting of a phosphate buffer (pH 7.2, 75 mM) with CTAB (50 mM) and ACN (30%) gave the best results. Linearity was established over the concentration range 0.5–500 μg/L and LODs from 65 to 775 ng/L; the interday precision was expressed as the RSD of the aldehydes ranging from 6.6 to 8.4%. Matrix effects were shown to be negligible by comparing the response factors obtained in ultrapure and treated waters. Aldehydes were readily determined at 1.1–8.4 μg/L levels in ozonated and chlorinated water samples, the method proposed being the first CE contribution developed for the systematic analysis of both aliphatic and aromatic LMMAs in water samples.